Autoimmune Channelopathies at Neuromuscular Junction - Huang, Kun; Luo, Yue-Bei; Yang, Huan (Frontiers in Neurology, 2019)
The neuromuscular junction, also called myoneural junction, is a site of chemical communication between a nerve fiber and a muscle cell. There are many types of channels at neuromuscular junction that play indispensable roles in neuromuscular signal transmission, such as voltage-gated calcium channels and voltage-gated potassium channels on presynaptic membrane, and acetylcholine receptors on postsynaptic membrane. Over the last two decades, our understanding of the role that autoantibodies play in neuromuscular junction disorders has been greatly improved. Antibodies against these channels cause a heterogeneous group of diseases such as Lambert-Eaton syndrome, Isaacs' syndrome and myasthenia gravis. Lambert-Eaton is characterized by late onset of fatigue, skeletal muscle weakness and autonomic symptoms. Patients with Isaacs' syndrome demonstrate muscle cramps and fasciculation. Myasthenia gravis is the most common autoimmune neuromuscular junction channelopathy characterized by fluctuation of muscle weakness. All these disorders have a high risk of tumor. Although these channelopathies share some common features, they differ for clinical features, antibodies profile, neurophysiological features and treatments. The purpose of this review is to give a comprehensive insight on recent advances in autoimmune channelopathies at the neuromuscular junction.